Analisis Kuat Tekan Beton Yang Dicampurkan Dengan Limbah Karet Ban Kendaraan Bekas - Yasan Muhamad Fikri; Komang Arya Utama; Rahmani Kadarningsih (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
The development of technology in concrete continues to experience innovation, such as the utilization of recycled tire rubber from vehicles. The use of waste tire rubber in concrete mixtures is one effort to reduce environmental pollution. However, the application of rubber waste in concrete mixtures needs to be studied further. Research on the use of recycled tire rubber as a partial replacement for fine aggregate in concrete with a target strength of 30 MPa and 40 MPa has been conducted. The use of rubber material was varied into several percentages: 0%, 4%, 8%, and 12% of the volume of fine aggregate, in addition to using 6% fly ash and 0.5% superplasticizer by weight of cement as additives. Compressive strength tests were conducted after the concrete had been submerged for 28 days. Based on the research results, an increase in compressive strength was obtained for the target strength of 30 MPa, where the compressive strength of concrete without rubber (0% rubber) reached 34.53 MPa, while with the use of 4% recycled tire rubber, the compressive strength decreased to 29.21 MPa. A similar trend was observed in concrete with a target strength of 40 MPa, where the compressive strength without rubber (0% rubber) could reach 41.77 MPa and decreased to 37.58 MPa after using 4% rubber.